Assistance in the QRIS Merchant Creation Process in Kampung Glintung Water Street - Synda Lailatus Nadiva; Anshari Malim Aksar; Nur Laely Hamzah; Wahju Wulandari; Wiwin Purnomowati (Trescode Green Organization, 2023)
This community service activity aimed to assist in the creation process of QRIS merchants in Kampung Glintung Water Street. Eight participating merchants were trained on how to register and activate their QRIS accounts. The training was conducted in two sessions, each session lasting for two hours. The results of the training showed that all of the participating merchants were able to successfully register and activate their QRIS accounts. The discussion section provides an overview of the benefits of QRIS for merchants and consumers. The conclusion states that the community service activity was successful in assisting the participating merchants in creating QRIS accounts.